南极雪的氢氧同位素组成 - 刘广山; 黄奕普; 金德秋; 周锡煌 (厦门大学, 2001)
测定了南极中山站至 Dome A沿线表层雪、中山站附近海冰上覆雪、新降雪和中山站附近湖水的 D和 18O,对内陆雪 δD和 δ18O随纬度和海拔高度的变化、海冰上覆雪 δD和 δ18O随深度的变化 ,各种雪中 δD和 δ18O之间的相关性进行了研究 【英文摘要】 The deuterium and 18 O in various Antarctic snow samples including the surface snow, which collected along the track from Station Zhongshan to Dome A, overlying snow on sea ice, fresh snow and lake water nearby Station Zhongshan, were measured. The results indicate that δ D and δ 18 O in the surface snow of Antarctic inland were negatively correlated with the latitude and the sea level elevation respectively. In the snow core from the overlying snow on sea ice, the depth distributions of. 国家自然科学基金重点项目!( 4 98360 10 );; 国家“九·五”科技攻关计划!( 98- 92 7- 0 1- 0 5)资助